Postharvest management of fresh produce : recent advances. - Singh, Bhim Pratap; Agnihotri, Shehar; Singh, Garima; Gupta, Vijai Kumar (Academic Press, 2023)
"Postharvest Management of Fresh Produce: Recent Advances critically addresses the latest issues, challenges, and technological advancements in postharvest management of fresh commodities, especially fruits, nuts, and vegetables. The book covers the intriguing correlation of preharvest treatments, maturity indices and postharvest operations that significantly affect the postharvest quality of fresh produce. Further topics include packaging, logistics and storage technologies, the role of microbial communities, and 'omics' strategies in postharvest disease management. Special attention is given to the latest trends of nanotechnology, internet of things (IoTs), and blockchain technologies in food supply chain management of perishable products." --Provided by publisher.